POSSIBILITIES OF USING MORPHOMETRIC MEASUREMENTS AS A TOOL TO ESTABLISH A LIVE BEEF CATTLE GRADING SYSTEM IN TUNISIA - A. Slimene; 2; C. Damergi; L. Chammakhi; T. Najar; M. Ben Mrad (Journal of Animal and Plant Sciences, 2021)
In the present study, a total of 273 bulls between 12 and 26 months of age were studied using morphometric measurements in order to establish a cattle grading system for beef cattle in Tunisia. The bulls were mainly Holstein (169), Limousin (16), Charolais (58), Salers (11), and crossbred animals (19). Measurements of the height at withers (WH) and pelvis (PH), the width (CW) and girth of the chest (CG), the width at pelvis (PW), and the depth of chest (CD), in addition to the weight and age at slaughter, were recorded. Statistical evaluations were made using of the principal component analysis (PCA) as well as a Ward’s cluster analysis (WCA). High correlations were recorded between the weight, the width at pelvis (r = 0.90), the chest width (r = 0.89), and the chest perimeter (r = 0.89). Principal components analysis identified two main components that could characterize the carcasses. Ward’s cluster analysis based on the two main components displayed the presence of four groups of bulls defined as following: (1) bulls with a low conformation and a small frame size, (2) bulls with a medium conformation and a large frame size, (3) bulls with fairly good conformation and a small frame size, and (4) bulls with a good conformation and a large frame size. Consequently, live weight and the height at withers can be used as the main measurements to establish a live cattle grading grid in Tunisia including a combination of live weight (light or heavy) and withers height (tall or short).
Keywords: Bulls; live measurements; classification; principal component; cluster analysis